HUBUNGAN PENGETAHUAN DENGAN KINERJA KADER POSYANDU: Studi Observasi Analitik Kader Posyandu di Wilayah Puskesmas Bangetayu Semarang - Fina Maudinda Putri; Purwito Soegeng Prasetijono (PT. Hasba Edukasi Mandiri, 2026)
Integrated Health Service Post (Posyandu) cadres are the spearhead of basic health services at the community level. Their performance is crucial for the success of promotive and preventive activities, particularly maternal and child health. One factor influencing cadre performance is their level of knowledge regarding the duties, functions, and implementation of Posyandu activities. This study aims to determine the relationship between knowledge and the performance of Posyandu cadres in the Bangetayu Community Health Center (Puskesmas Bangetayu) work area. This was an observational study with a cross-sectional design. Subjects were 76 Posyandu cadres at Bangetayu Community Health Center, selected using consecutive sampling. Data were collected using a questionnaire on cadre knowledge and performance, which had been tested for validity and reliability. Data were analyzed univariately to describe the distribution of respondent characteristics, and bivariately using the Pearson correlation test. The results showed that the majority of cadres had knowledge levels in the sufficient (46.1%) and good (35.5%) categories. Cadre performance fell into the good and sufficient categories, respectively, at 34.2%, while 31.6% were in the poor category. Bivariate analysis showed a significant relationship between knowledge level and Posyandu cadre performance, with a p-value < 0.001 and a correlation coefficient of r = 0.438, indicating a positive relationship with moderate strength. It can be concluded that knowledge is significantly related to Posyandu cadre performance.